Development and Characterization of Microsatellite Loci for Smooth Cordgrass, Spartina alterniflora (Poaceae) - Wuxia Guo; Yelin Huang; Ziwen He; Yubin Yan; Renchao Zhou; Suhua Shi (Applications in Plant Sciences, 2013)
Premise of the study: Spartina alterniflora is one of the nine most notoriously invasive plants in China. Microsatellite markers were developed for this species to investigate its invasiveness and genetic diversity.